PERJANJIAN JUAL BELI E-COMERCE DITINJAU DARI HUKUM PERJANJIAN DAN UNDANG-UNDANG INFORMASI DAN TRANSASI ELEKTRONIK - Gunadi (Ahwaluna | Jurnal Hukum Keluarga Islam, 2024)
In a sale and purchase agreement over the internet, the transaction is not the same as a conventional sale and purchase agreement where the seller and buyer meet face to face. This raises the question of when an agreement occurs. To answer this, we can use the Acceptance Theory which teaches that an agreement occurs when the offering party directly receives an answer from the opposing party. The agreement between the seller and the buyer occurs when the seller receives an answer from the buyer. This can be done by several methods, namely through a single click, "double click to three clicks. Basically, the provisions of Article 1458 of the Civil Code still apply. That an agreement is deemed to have occurred when one party agrees (agrees) on the subject of the agreement stated by the other party. This statement is the basis for the agreement (statement of will) of the two parties. The validity of a sale and purchase agreement through e-commerce is the same as a conventional sale and purchase agreement because of the fulfillment of the valid terms of the agreement stipulated in Article 1320 of the Civil Code.